High temperatures and antibacterial plant additives change the fermentation quality, free amino acids and lactic acid bacteria fermentation type in Caragana Korshinskii silage - Tong Zhou; Xingcheng Lei; Yimei Luo; Yangwen Ou; Simin Tian; Yixiao Xie; Yulong Zheng; Hong Sun; Fuyu Yang (BMC Microbiology)
Abstract Background High temperatures cause a significant loss of dominant lactic acid bacteria (LAB) and the proliferation of harmful microorganisms during ensiling. The current study aimed to investigate the effects of tea residue (TR), mugwort (AA), and molasses (CMA) on silage quality, free amino acid content, and the bacterial community of Caragana korshinskii (C. korshinskii) with Lactobacillus plantarum (LP) at 40 °C. Results Compared to those at the control temperature (25 °C), the concentration of lactic acid and the number of LAB in all treatments decreased with the progression of fermentation at 40 °C; however, the ammoniacal nitrogen (NH3-N) and propionic acid concentrations increased after 14 days. The levels of 15 free amino acids initially increased and then decreased. The fermentation temperature significantly affected the diversity of the bacterial community, with the community succession transitioning from Lactiplantibacillus to Lactobacillus, Stenotrophomonas_A_615274, Salinivibrio, and other genera during the fermentation process. TR + LP treatment resulted in a 48.9% increase in crude protein content and a 46.4% decrease in NH3-N content at 40 ℃. LP only and AA + LP treatments elevated acetic acid (HAc) levels and the relative abundance of Lactobacillus while reducing other bacterial diversity at 40 °C. Conclusion The integration of LAB with plant-derived additives improved the fermentation quality of C. korshinskii silage by decreasing both NH3-N production and harmful bacterial abundance under high-temperature conditions. The TR + LP treatment group increased the nutritional quality of C. korshinskii silage. The LP and AA + LP treatment groups had a bacteriostatic effect, but no significant effect on improving nutritional quality in C. korshinskii silage.